2009
DOI: 10.1371/journal.pone.0005672
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy Using Chimeric Monoclonal Antibodies Protects Mice from Lethal H5N1 Infection and Prevents Formation of Escape Mutants

Abstract: BackgroundGiven that there is a possibility of a human H5N1 pandemic and the fact that the recent H5N1 viruses are resistant to the anti-viral drugs, newer strategies for effective therapy are warranted. Previous studies show that single mAbs in immune prophylaxis can be protective against H5N1 infection. But a single mAb may not be effective in neutralization of a broad range of different strains of H5N1 and control of potential neutralization escape mutants.Methods/Principal FindingsWe selected two mAbs whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 29 publications
2
45
0
1
Order By: Relevance
“…In this regard, DPJY01 shows remarkable activity against H5N1 infection under prophylactic and therapeutic conditions. Previous studies have shown the potential of IgG MAbs for passive immunotherapy against H5N1 influenza virus when administered parentally (4,9,18,19,24,27,28,30,38). Instead, we developed an IgA MAb that can be administered intranasally.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, DPJY01 shows remarkable activity against H5N1 infection under prophylactic and therapeutic conditions. Previous studies have shown the potential of IgG MAbs for passive immunotherapy against H5N1 influenza virus when administered parentally (4,9,18,19,24,27,28,30,38). Instead, we developed an IgA MAb that can be administered intranasally.…”
Section: Discussionmentioning
confidence: 99%
“…Research groups, including ours, have attempted to characterize MAbs which bind to the conserved epitopes located on the HA1 subunit (7,25,31). Recently, several studies have reported on MAbs which recognize a highly conserved helical region in the membrane-proximal stem of HA1/HA2 and which demonstrate heterosubtypic neutralizing abilities against H1, H2, H5, H6, H8, and H9 subtype viruses (10,30,33).…”
Section: Discussionmentioning
confidence: 99%
“…The HA2 subunit, which is primarily responsible for mediating the fusion of viral and cell membranes, is relatively conserved among different subtypes of influenza viruses. While most H5N1-specific antibodies have been found to target the HA1 region (7,21,25,31), several recent studies have reported on antibodies with the potential to neutralize influenza viruses of different subtypes by targeting the HA2 region of the HA protein (10,12,15,30,33).…”
mentioning
confidence: 99%
“…This problem may be overcome by using mixtures of mAbs that target various areas of bio-threat agents. Several studies demonstrated that combination therapy with mAb cocktails could prevent escape variants for many viruses including influenza, coronavirus, and lymphocytic choriomeningitis virus [50][51][52]. Also, a cocktail of functional mAbs could provide more protection and target more microbial strains than a single one.…”
Section: Cocktail Of Mabsmentioning
confidence: 99%